Large polarization-dependent exciton optical Stark effect in lead iodide perovskites - Ye Yang (Nature Portfolio, 2016)
The band gap of bulk semiconductors widens when excited by sub-bandgap wavelengths at low temperature—it’s the optical Stark effect. Here, the authors measure a room temperature optical Stark effect in lead halide perovskite films, due to their well-resolved excitonic transitions.